(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2026)
The research examined the functional properties of defatted wheat germ protein isolate (DWGPI) and compared it with commercial casein. The results of the chemical composition of samples raw wheat germ RWG, defatted wheat germ DWG and DWGPI showed that DWGPI was higher than RWG and DWG in protein content (86.18) %, and DWG was higher in carbohydrate content (58) %, while the highest percentage of fat and moisture reached (11.8, 9.5) % in the RWG sample. respectively. In addition, the functional properties of wheat germ protein isolate (DWGPI) were compared with commercial casein protein. The solubility at different levels of pH for both samples showed that the highest percentage of solubility at pH 12 was (70.5, 65.6) %, respectively, and the lowest percentage of solubility at pH 4 was (13.3, 12.8) %, respectively. While the highest ability to emulsify was (86, 83) % at pH 12 and (75, 65.6) % for emulsion stability for both protein isolate and casein samples, respectively. While the highest value of foaming ability was at pH 12, about 82% and 74%, and the lowest value was at pH 4, about 12% and 8% for protein isolate and casein, respectively. As for foam stability at different pH levels and times, the highest value at pH 12 was (90, 84, 73, 72) % for protein isolate and (87, 75, 64, 60) % for casein, and the lowest value was at pH 4. The highest value for water absorption at pH 10 was (6.36, 11.1) ml water/gm protein, and the lowest value at pH 4 was (1.49, 2.05) ml water/gm protein for protein isolate and casein, respectively. While the fat holding capacity of the protein isolate was (1.74) ml oil/gm protein and for casein (1.32) ml oil/gm protein.